Data for Use of Deputy Chairman Planning Commission - Planning Commission (Planning Commission, 2012)
India - Macro-economic Summary : 1999-00 to 2011-12 Economy at a Glance : India (1999-2000 to 2011-12) - Graphical View Indian Economy : Some Indicators (91-92 to 11-12) Indian Economy : Some Indicators - Ninth Tenth and Eleventh Plans, etc., India - Macro-economic Summary and GDP by Activities (YoY) and other Economy Indicators : 1999-2000 to 2011-12 Select Economic and Social Indicators - India (1950-51 to 2010-11) Macro-economic Balances - Indicators 2004-05 Series : 2001-02 to 2011-12 and Plan-wise Selected Indicators of Development Central Government: Receipts and Expenditure with % of GDP (at current market prices) 2006-07 to 2012-13 (BE) Central Government: Revenue, Expenditure and Fiscal Deficit (% of GDP at current market prices) 1992-93 to 2012-13 (BE) Gross Fixed Capital Formation by Type of Institution (93-94 to 10-11) Domestic Savings by Type of Institution and Rate of Savings : 2004-05 to 2010-11.
Planning Commission Government of India
Planning Commission Government of India